Biological differences between functionalis and basalis endometria in women with and without adenomyosis. (August 2016) - Khan, Khaleque N.; Fujishita, Akira; Kitajima, Michio; Masuzaki, Hideaki; Nakashima, Masahiro; Kitawaki, Jo
Abstract: Objective: Endometriosis is commonly believed to originate from functionalis endometrium and adenomyosis from basalis endometrium. Due to the lack of enough information, we investigated the biological differences between these two layers of endometrium in women with and without adenomyosis. Study design: This was a case-controlled study with 12 control women and 17 women with adenomyosis undergoing hysterectomy. Full thickness (extending from the endometrium to the myometrium) biopsy specimens were obtained after the hysterectomy. Based on the phases of the menstrual cycle, the expression patterns of estrogen receptor (ER), progesterone receptor (PR), Ki-67, and activated Caspase-3 were analyzed by immunohistochemistry in the functionalis and basalis endometria. Apoptotic cells were evaluated by TdT-mediated dUTP-biotin nick end-labeling (TUNEL) assay. Results: A similar pattern of ER and PR expression was found in the functionalis and basalis endometria during the proliferative phase. In contrast, a significantly lower ER and PR expression was found in the basalis endometria than in the functionalis endometria during the secretory phase and the menstrual phase. This was equally observed in control women and in women with adenomyosis. Except Ki-67 indices, TUNEL-positive cells, and expression of activated Caspase-3 were significantly lower in the basalis endometria than in the functionalis endometria during the secretory phase. Conclusion: A significant biological difference was found between the functionalis and the basalis endometria derived from women with adenomyosis.